Cognitive representations of spatial location. (November 2018) - Jeffery, Kate J.
Spatial memory has fascinated psychologists ever since the discipline began, but a series of findings beginning in the middle of last century propelled its study into the domain of neuroscience and helped bring about the cognitive revolution in psychology. Starting with the discovery that the hippocampus plays a central role in memory, particularly spatial memory, studies of the mammalian hippocampus and related regions over the latter half of the century slowly uncovered an extensive neural system involved in processing place, head direction, objects, speed and other spatially informative parameters. Meanwhile, the concurrent discovery of hippocampal synaptic plasticity allowed theoreticians and experimentalists to collaborate in linking spatial perception and memory, and genetic techniques developed towards the end of the century opened the door to circuit dissections of these processes. Building on these discoveries, spatial cognition and episodic memory may be the first cognitive competences understood across all levels from molecules to behaviour.